Academic and Psychosocial Outcomes of a Physical Activity Program With Fourth Graders: Variations Among Schools in Six Urban School Districts. (November 2019) - Somers, Cheryl L.; Centeio, Erin E.; Kulik, Noel; Garn, Alex; Martin, Jeffrey; Shen, Bo; Fahlman, Mariane; McCaughtry, Nathan A.
The purpose was to examine academic achievement, school attachment, and peer acceptance before and after a comprehensive school-based physical activity program (CSPAP) with 378 children in 12 fourth-grade classrooms across six schools in primarily low-socioeconomic status (SES) districts of a large Midwestern metropolitan area. Both personal and normative rate of academic achievement improvement metrics were used. Overall, all students showed personal math and reading growth. However, effects varied by types of achievement indicator and comparison group, revealing noteworthy school-level demographic and implementation characteristics that are inextricably intertwined with program effectiveness and student growth. Implications, especially for minimizing generalizations, are significant.